Antibiotic Use Evaluation Based on AWaRe Classification in Hospitalized Patients (Intensive and Non-Intensive Care) at Universitas Indonesia Hospital - Nadia Farhanah Syafhan; Sri Wulandah Fitriani; Dinda Bestari Sutantoputri; Nadhila Hasna Hanifah; Adityo Susilo (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Antibiotic stewardship program has been largely implemented to reduce antibiotic resistance rates. The present study aimed to evaluate antibiotic use based on the AWaRe classification using the ATC/DDD method and Drug Utilization 90% (DU 90%). This analytical descriptive study used a cross-sectional study design and retrospective data collection obtained using a total sampling technique and processed using Microsoft Excel. The sample for this study involved data from inpatients aged ≥ 18 years at Universitas Indonesia Hospital who had been prescribed antibiotics from 1 January - 31 December 2022. Data from patients who only received topical antibiotic or antibiotics without a DDD standard value from WHO, or patients who had incomplete medical record data were excluded from the study. The results of this study indicated that the total use of antibiotics was 427.85 DDD/100 patient-days. Based on the AWaRe (Access, Watch, Reserve) classification, the Watch class became the most frequently used antibiotic group, followed by the Access and Reserve classes. The 90% DU segment was mostly composed of third-generation cephalosporin group and fluoroquinolones which were included in the Watch class. From the result of this study, to optimally reduce resistance rates, antibiotic stewardship programs need to run continuously.